Pengaruh Model Pembelajaran Discovery Learning terhadap Hasil Belajar IPA - Aisyah Ramadani; Afridha Bachtiar; Muh. Hasbi Assidiq R.; Kharisma Saputri; Rahmatia Thahir; Hasmunarti Hasmunarti (Universitas Palan, 2024)
written in English, referring to the article written. The abstract contains concise statements about the most important ideas. Abstracts contain problems and research objectives, research procedures (for qualitative research including descriptions of the subjects studied), and summaries of research results (if deemed necessary, also conclusions and implications). Emphasis is placed on research results. Other things such as hypotheses,discussions, and suggestions are not presented. Maximum abstract length is 200 words and written in one paragraph. Keywords are the main words that describe the problem area being investigated or terms that are the basis for the idea of ideas in the original essay, in the form of a single word or a combination of words. The tems. With keywords you can easily find research titles and abstracts.